A Clinical Study to Evaluate the Effect of Gomutra Arka Parisheka and Jathyadi Ghrita Application in Dushta Vrana w.s.r. to Non-Healing Ulcers (International Journal of Ayurveda and Pharma Research, 2023)
Vrana is derived from the word ‘Vran’ which means one which causes destruction and discoloration of the body parts. Current estimates indicate nearly 6 million people suffer from chronic wound worldwide. Wounds can significantly interfere with quality of life of the patient. It can also complicate into gangrene, septicemia and death. Sushruta Acharya explains the features of Dushta Vrana. Shashtir Upakrama is mentioned as management for Vrana. Gomutra is one among the Parisheka Upakrama Dravya as well as in Krimighna Upakrama Dravya. Jathyadi gritha is prescribed as Vrana ropaka. An effort is made to evaluate the effect of Gomutra Arka Parisheka followed by Jathyadi Ghrita topical application in Dushta Vrana. It is a single group open labelled, randomized clinical study with pre test and post test design. 30 patients diagnosed with Dushta vrana fulfilling the inclusion criteria were selected for clinical trial with consent and subjected to Gomutra Arka parisheka with Jatyadhi Ghrita application followed by internal medications. The Parisheka and application was done for 7 days, data is recorded daily. Data obtained were recorded and statically analyzed. The treatment showed significant clinical improvement in controlling of pain, itching, foul smell and discharge. Clinical study showed good improvement in healing of ulcers in terms of clearing of slough, formation of granulation tissue and wound contraction.